Inhibitory Effect of Volatiles Emitted From Alcaligenes faecalis N1-4 on Aspergillus flavus and Aflatoxins in Storage - Gong, An-Dong; Wu, Nan-Nan; Kong, Xian-Wei; Zhang, Yi-Mei; Hu, Meng-Jun; Gong, Shuang-Jun; Dong, Fei-Yan; Wang, Jian-Hua; Zhao, Zhi-Yong; Liao, Yu-Cai (Frontiers in Microbiology, 2019)
Controlling aflatoxigenic Aspergillus flavus and aflatoxins (AFs) in grains and food during storage is a great challenge to humans worldwide. Alcaligenes faecalis N1-4 isolated from tea rhizosphere soil can produce abundant antifungal volatiles, and greatly inhibited the growth of A. flavus in un-contacted face-to-face dual culture testing. Gas chromatography tandem mass spectrometry revealed that dimethyl disulfide (DMDS) and methyl isovalerate (MI) were two abundant compounds in the volatile profiles of N1-4. DMDS was found to have the highest relative abundance (69.90%, to the total peak area) in N1-4, which prevented the conidia germination and mycelial growth of A. flavus at 50 and 100 μL/L, respectively. The effective concentration for MI against A. flavus is 200 μL/L. Additionally, Real-time quantitative PCR analysis proved that the expression of 12 important genes in aflatoxin biosynthesis pathway was reduced by these volatiles, and eight genes were down regulated by 4.39 to 32.25-folds compared to control treatment with significant differences. And the A. flavus infection and AFs contamination in groundnut, maize, rice and soybean of high water activity were completely inhibited by volatiles from N1-4 in storage. Scanning electron microscope further proved that A. flavus conidia inoculated on peanuts surface were severely damaged by volatiles from N1-4. Furthermore, strain N1-4 showed broad and antifungal activity to other six important plant pathogens including Fusarium graminearum, F. equiseti, Alternaria alternata, Botrytis cinerea, Aspergillus niger, and Colletotrichum graminicola. Thus, A. faecalis N1-4 and volatile DMDS and MI may have potential to be used as biocontrol agents to control A. flavus and AFs during storage.